EFFECT OF DIVERSITY MANAGEMENT ON HUMAN RESOURCE MANAGEMENT: RECRUITMENT AND SELECTION IN FOCUS - Okolie, Ugo Chuks (Annals of Spiru Haret University. Economic Series, 2020)
Abstract The changing demographic composition of the workforce, the overall effects of globalization and the increasing social sensitivity to ethical concerns are compelling multinational organizations to deal with diversity management. However, organizations worldwide, in their attempt at diversity management have faced challenges as stereotypes are deeply rooted in one’s culture and there is resistance to change. The key to diversity management hinges on strategic thinking and people centered policies. It is against this backdrop that this paper examines the effects of diversity management on human resource management with special reference to recruitment and selection. In this paper, we explore the interface between diversity management and human resource management and how this impinges on recruitment and selection when HR managers fails to acknowledge cultural and individual differences in the workplace, focus attention on individual differences rather than group differences; we develop a conceptual framework of HR diversity management, linking HR diversity strategies with major HR diversity issues; we also, examine the state of HR diversity practices that have been adopted in organizations worldwide and finally we discuss the gaps in the literature and the implications of our findings for practitioners and researchers